Synthesis of SiBNC‐Al ceramics with different aluminum contents via polymer‐derived method. Issue 4 (21st December 2021) - Tang, Zicheng; Wang, Shaofei; Tusiime, Rogers; Hu, Jidong; Chen, Haikun; Zhang, Yifan; Zhang, Hui; Liu, Yong
Abstract: This study reports the synthesis of three types of aluminium (Al)‐modified polyborosilazane ceramic precursors (PBSAZ) from C8 H19 Al/HSiCl3 /HMDZ/BCl3 and their thermal conversion to SiBNC‐Al ceramics at 1000°C. FT‐IR, nuclear magnetic resonance (NMR), X‐ray photoelectron spectroscopy (XPS), and thermogravimetric analysis (TGA) are used to characterize the structures and properties of the PBSAZ. PBSAZ is found to be built up of the Si─N─B framework, with Al successfully introduced into the ceramic network structures. The ceramic yield is 63.5 wt.% for the Al‐poor polymers (PBSAZ‐5) and 65.1 wt.% for the Al‐rich polymers (PBSAZ‐1). The high‐temperature cracking behavior and the crystal phase structures of the ceramics were characterized by XRD and Raman, which revealed that SiBNC‐Al ceramics contained Si4 N3, SiC, and AlN (+SiC) crystals after heat treatment at 1600°C. The oxidation behavior of SiBNC and SiBNC‐Al ceramics at 1500°C shows that the introduction of Al improves the quality of the oxide layer, effectively suppresses the oxide layer cracking phenomenon, and reduces gas bubble generation.